1997
DOI: 10.1086/514891
|View full text |Cite
|
Sign up to set email alerts
|

Genome Scanning for Segments Shared Identical by Descent among Distant Relatives in Isolated Populations

Abstract: In this paper, we address some of the statistical issues concerning false-positive rates that arise when the whole genome, or a portion thereof, is scanned in distantly related individuals, to search for a disease locus. We derive a method for correcting false-positive probabilities for the large number of comparisons that are performed when scanning a large portion of the genome. We consider both the idealized situation of a dense set of fully informative markers and the more realistic data-collection strateg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
44
0

Year Published

1998
1998
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(46 citation statements)
references
References 10 publications
(38 reference statements)
2
44
0
Order By: Relevance
“…Furthermore, a haplotype (271-2) of the two-marker segments D3S3594-D3S3589 at 32.36 cM was close to significantly more frequent among cases than controls, and the probability (P 0 and P 1 ) that six out of 22 haplotypes are shared IBD 0 in cases related 7.2 generations ago is as small as 2.7 Â 10 À8 and 1.7 Â 10 À7 , respectively, according to the formula of Houwen 39 and P 2 ¼ 3.7 Â 10 À5 according to Durham and Feingold. 40 The frequency of allele 206 of marker D15S198 on chromosome 15q also appeared to be significantly different among cases compared to controls. A single haplotype (206-7) of the twomarker segment D15S198-D15S643, spanning 51.21-52.33 cM, proved to have significantly higher frequency among cases compared to controls, and IBD 0 calculations showed that IBD 0 is less likely.…”
Section: Resultsmentioning
confidence: 93%
See 2 more Smart Citations
“…Furthermore, a haplotype (271-2) of the two-marker segments D3S3594-D3S3589 at 32.36 cM was close to significantly more frequent among cases than controls, and the probability (P 0 and P 1 ) that six out of 22 haplotypes are shared IBD 0 in cases related 7.2 generations ago is as small as 2.7 Â 10 À8 and 1.7 Â 10 À7 , respectively, according to the formula of Houwen 39 and P 2 ¼ 3.7 Â 10 À5 according to Durham and Feingold. 40 The frequency of allele 206 of marker D15S198 on chromosome 15q also appeared to be significantly different among cases compared to controls. A single haplotype (206-7) of the twomarker segment D15S198-D15S643, spanning 51.21-52.33 cM, proved to have significantly higher frequency among cases compared to controls, and IBD 0 calculations showed that IBD 0 is less likely.…”
Section: Resultsmentioning
confidence: 93%
“…In order to determine whether a potential association between autism and related PDDs and single-or two-marker segments is due to IBD 0 , the probability that affected individuals share a haplotype that is IBD 0 from a known ancestor through a specific genealogical relationship was calculated using the formulas derived by Houwen et al 39 and Durham & Feingold. 40 In these formulas, the average pairwise relationship with a common ancestor of the 12 individuals with autism and related PDDs were used. P 0 is the probability of the observed number of cases having the most frequent haplotype IBD 0 from a known ancestor (i.e.…”
Section: Atypical Autismmentioning
confidence: 99%
See 1 more Smart Citation
“…The failure to detect other haplotypes could depend on insufficient density of the present marker map, or on the use of a limited number of affected individuals in the first screen in which only five patients were genotyped extensively. Durham and Freingold, 29 using a simulation analysis, proposed that the median size of a segment shared IBD by five chromosomes, with a separation distance of six meiosis, is only *5.5 cM. Therefore, an optimal analysis of the present material might require an increased number of nuclear families in an initial screen and a denser marker map.…”
Section: Discussionmentioning
confidence: 99%
“…The chance of a false positive finding in a genome-wide analysis such as the present must be taken into account, although the theoretical risk has been evaluated using simulation analysis. 15,29 In general, the shared haplotype method is considered to give a low rate of false positives. To minimise false positive findings in the initial screen, we set up the strict criteria outlined above.…”
Section: Discussionmentioning
confidence: 99%